MODIFIKASI TOP CYCLONE UNTUK MENINGKATKAN KINERJA SUATU PABRIK SEMEN - Darmanto, Prihadi Setyo; Syahlan, Arief (Mesin, 2006)
Clinker production of a cement plant can be increased by rising clinker to kiln feed ratio-CKFR. One of the methods for increasing CKFR is by improving the separating efficiency of the top cyclone. The increase of separating efficiency of the top cyclone causes not only the increase of production, but is also followed by the lowering of specific heat consumption and percentage of ash in the coal because the exit gas from thetop cyclone is normally used for coal drying. This paper presents a simple and cheap modification of the top cyclone that has been applied in a Indonesian cement plant. The results show that the proposed modification can simultaneously increase clinker production, lower both of specific heat consumption and percentage of ash in the fine coal that used as the main fuel of the plant.